Optimization of phosphorus content in high plant protein practical diets for Senegalese sole (Solea senegalensis, Kaup 1858) juveniles: influence on growth performance and composition of whole body and vertebrae - Salas-Leiton, E.; Dias, Joaquim; J. Gavaia, Paulo; Amoedo, A.; Valente, L. M. P. (Aquaculture Nutrition, 2017)
Practical diets containing PP sources were elaborated. Increasing levels of di-calcium phosphate were added to diets leading to five different dietary available P levels: 2.5, 3.2, 6.0, 6.5 and 8.0 g kg(-1) dry diet. The dietary treatments were tested in 13.5 g Senegalese sole juveniles throughout an 82-day experimental period. Dietary P content had no effect on the productive parameters, while nutrient intake was also similar among dietary treatments, except P intake. Dry matter ADC ranged between 54.9% and 64.0%, and the highest P ADCs value (47.2 +/- 0.7%) was achieved in fish fed AP6.0. Dietary phosphorus level significantly influenced body lipid and P compositions. Regression analysis performed on whole-body P and ash contents fitted to quadratic models. Vertebral bone P content was low but increased significantly with increasing dietary P levels. Bone density and deformities occurrence were, however, similar between experimental conditions. An altered status of bone formation-resorption processes in soles fed the lowest P content diet might be inferred from ALP and TRAP activities. In conclusion, overall results state a high tolerance of Senegalese sole to low P content diets and support the utilization of practical diets with high plant protein content. North Region Operational Programme (ON. 2 - O Novo Norte), under the project Sustainable Aquaculture and Animal Welfare (AQUAIMPROV) [NORTE-07-0124-FEDER-000038] info:eu-repo/semantics/publishedVersion